Narrative, Nature-Based Participatory Action Research (PAR) among Female Turkish Migrants in Denmark: Reflections on Methodological Benefits and Challenges - Anne Leonora Blaakilde; Karen Christensen (Societies, 2024)
Migrants of non-European origin tend to suffer more from diabetes, obesity and other chronic ailments compared to the native population. A group of female Turkish migrants in ill health, living in Denmark, were invited to join a session of eleven weekly meetings in natural surroundings, including yoga, bonfires and gathering fruits and herbs. The women were invited to suggest activities, and every meeting included dialogues focusing on their everyday life, interests and experiences. Two PAR researchers facilitated the meetings together with an interpreter. This article presents the methods and results of this PAR research and discusses the methodological ethnographic balance between approaching the migrants’ weaknesses in terms of their illness and migratory challenges on the one hand and, on the other, their transnational resources as workers, household keepers and kin keepers.